PENGARUH MODEL PEMBELAJARAN PROBLEM-BASED LEARNING (PBL) TERHADAP HASIL BELAJAR SISWA MATERI USAHA DAN ENERGI DI KELAS XI SMA NEGERI - Zuliani Nasution, Unita Sukma (Jurnal Physics Education (PhysEdu), 2024)
This study aims to know whether there is a significant effect of using Problem Based Learning (PBL) model on students’ physic achievement on the topic effort and energy at the eleventh grade students of SMA Negeri 1 Barumun Selatan. The research was conducted for 3 months (July –September 2017) by using experimental method. The total sample was 50 students and it was taken by using total sampling technique. Observation and test were used in collecting the data. Based on descriptive analyzes, it could be found that a) the average of using PBL model was 93.33 (very good category) and the average of students’ physic achievement on the topic effort and energy before using PBL model 66.92 (enough category) and after using PBL model was 83.07 (very good category). Furthermore, based on inferential statistic by using ttest, the result showed that the value of tobserved is greater than ttable (13.88>1.71), it means, there is a significant effect of using Problem Based Learning (PBL) model on students’ physic achievement on the topic effort and energy at the eleventh grade students of SMA Negeri 1 Barumun Selatan.